2021
DOI: 10.1210/clinem/dgab025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spectrum of DICER1 Mutations in Adult-onset Thyroid Nodules with Indeterminate Cytology

Abstract: Context DICER1 mutations are found in multinodular goiter and differentiated thyroid carcinoma in children, and can be a manifestation of DICER1 syndrome, but the prevalence of DICER1 mutations and their significance in adult-onset thyroid nodules is unknown. Objective Determine 1) the prevalence of DICER1 hotspot mutations in thyroid nodules; 2) the frequency of a second DICER1 pathogenic variant in thyroid nodules with DICE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 34 publications
4
37
1
Order By: Relevance
“…Therefore, it is possible that the DGCR8 mutation found in these tumors influenced the tumor progression or invasive behavior without driving the tumor formation per se. However, recent studies have found recurrent DICER1 mutations in various forms of thyroid cancer, of which most cases did not display established driver-gene alterations, vaguely suggesting that aberrant miRNA expressional patterns could be at play even at the level of tumor initiation ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the DGCR8 mutation found in these tumors influenced the tumor progression or invasive behavior without driving the tumor formation per se. However, recent studies have found recurrent DICER1 mutations in various forms of thyroid cancer, of which most cases did not display established driver-gene alterations, vaguely suggesting that aberrant miRNA expressional patterns could be at play even at the level of tumor initiation ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DICER1 mutated thyroid tumors in both adult and pediatric patients have been shown by several groups to be mutually exclusive of any of the well-known driver mutations of thyroid cancer (including BRAF and RAS among others). This provides evidence that DICER1 mutation can be a driver of thyroid tumor development (76,77) and establishes another link between miRNA dysregulation and thyroid cancer. Furthermore, the role of DICER1 down-regulation and subsequently miRNA dysregulation has been shown in vitro.…”
Section: Discussionmentioning
confidence: 61%
“…100 In adults, DICER1 alterations are found in approximately 1% of indeterminate thyroid nodules. 101 2.9.1 | MicroRNA alterations MicroRNAs (miRNAs) are small, single-stranded, and noncoding RNA molecules. These molecules regulate genes at the posttranscriptional level and are part of the RNA-induced silencing complex; downregulating the expression of other genes by increasing degradation of the target transcript or inhibiting translation.…”
Section: Pten Mutations and Loss Of Heterozygositymentioning
confidence: 99%
“…In a cohort of 15 patients with FTC less than 20 years old, 8 patients had DICER1 mutations; DICER1 alterations were found in co‐occurring nodular hyperplasia and follicular adenomas 100 . In adults, DICER1 alterations are found in approximately 1% of indeterminate thyroid nodules 101 …”
Section: Common Genetic Alterationsmentioning
confidence: 99%